Epothilone B induces glioblastoma cell death via survivin down-regulation - Quick, Q.A. (Experimental Oncology, 2008)
The clinical resistance of glioblastomas to chemotherapeutic agents can be attributed to drug efflux pumps, such as P-glycoprotein, which contributes to reduce drug efficacy. The present study examined the utility of epothilone B, which is not a substrate for P-glycoprotein, on glioblastoma cells. Methods: In vitro methods with glioblastoma cells varying in p53 status were used to assess the efficacy of epothilone B to induce anti-neoplastic responses. Immunofluorescence and ELISA procedures were used to examine levels of tubulin and survivin in epothilone B treated glioblastoma cells, while acridine orange labeling was used to detect the mode of epothilone B induced cell death. Results: A clinically achievable concentration of epothilone B induced a cytotoxic response in p53 mutant glioblastoma cells, as a consequence of survivin down-regulation and tubulin redistribution, while a cytostatic response was observed in p53 null glioblastoma cells with a modest increase in survivin expression post-epothilone B treatment. However, p53 wild-type glioblastoma cells did not sustain a positive anti-tumorigenic response to epothilone B. Conclusion: Epothilone B, induced positive differential responses in glioblastoma cells with abnormal p53 status, but not in p53 wild-type cells. This suggests that epothilone B is a potential alternative to classic microtubule inhibiting agents (ie vincristine, paclitaxel) used to treat clinical glioblastomas with p53 mutations. Клиническая резистентность глиобластом к химиотерапии может быть объяснена действием насосов, откачивающих препараты,
подобные P-гликопротеину, которые играют важную роль в снижении эффективности лекарственных средств.
Цель: изучить возможность применения эпотилона В, не являющегося субстратом для Р-гликопротеина, для воздействия
на глиобластомные клетки. Методы: для оценки эффективности эпотилона В как антинеопластического препарата в работе
in vitro использованы клеточные линии глиобластомы, отличающиеся по статусу p53. Для оценки уровня экспрессии
тубулина и сурвивина в клетках, обработанных эпотилоном В, были использованы методы иммунофлуоресценции и ELISA.
Окрашивание акридиновым оранжевым применяли для детекции погибших клеток после обработки эпотилоном В. Результаты:
клинически достижимые концентрации эпотилона В оказывали цитотоксический ответ на клетки глиобластомы с
мутантным р53 в результате снижения уровня сурвивина и перераспределения тубулина. В то же время цитостатический
эффект наблюдали и на клетках глиобластомы, не экспрессирующих р53, что сопровождалось небольшим повышнием
экпрессии сурвивина после обработки клеток эпотилоном В. Однако на клетках глиобластомы с р53 дикого типа не было
выявлено антиопухолевого ответа на эпотилон В. Выводы: эпотилон В вызывает различный противоопухолевый ответ
в клетках глиобластомы, экспрессирующих мутантный р53, либо отрицательных по р53. Это позволяет предположить, что
эпотилон В является альтернативой классическим препаратам, ингибирующим микротрубочки (например винкристину,
паклитакселу), которые используют в клинической практике при лечении глиобластом с мутантным белком р53.